A practical guide for the use of very low calorie diets in adults with chronic kidney disease. Issue 4 (27th November 2019) - Lambert, Kelly; Bahceci, Su; Lucan, Beth; Ryan, Murielle
Abstract: Obesity is increasingly common in individuals with chronic kidney disease (CKD). Being overweight or obese is associated with both the development and progression of kidney disease. Lifestyle interventions such as the use of very low‐calorie diets (VLCD) are being used increasingly for patients with CKD despite warnings from manufacturers that they should be avoided or used with caution. Whilst these diets are effective and can induce rapid weight loss and suppress appetite, their use in patients with chronic and end stage kidney disease is more complex than in the general population. VLCD use in adults with kidney disease requires a more nuanced approach to prescription and closer monitoring for unintended side effects. This review describes the indications and clinical management of patients with CKD undertaking a very low‐calorie diet and provides practical guidance regarding how to manage a VLCD, particularly for the latter stages of CKD. SUMMARY AT A GLANCE: This review examines the use of very low‐calorie diets among patients with chronic kidney disease and provides a practical resource describing the indications and complications of these diets in CKD.